Journalism in the digital age: trends and threads - Seifullina, Z. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
In the globalised world the Internet is becoming extremely globalised. Freedom of speech and easy access to the information are praised. But how much can the Internet be good for people, especially for their most vulnerable part, such as children? This paper contributes to the discussion on protecting children from access to pornographic content. The topic of the article has a global significance. This paper contributes to the discussion on protecting children from access to pornographic content but has a global significance. Internet and mobile device usage have become a central feature in children’s lives. Taking into account the growing availability of prohibited content such as pornography to children, it seems appropriate to launch certain measures in order to restrict kids’ access to this. In addition, this consultation addresses many socially important research topics and answer several questions in this essay. In particular, whether age verification controls should be placed on all forms of legal pornography (‘sex works’) online that would receive a British Board of Film Classification rating of 18 or R18 or not; should this measure be implemented for websites containing still and moving images of pornography and which methods should be used in order to conduct age verification online.